Tourism Dynamic Assessment Using Geospatial Approach in Bageshwar District, Uttarakhand - Gill, N; Singh, R P (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Dynamics of tourism is a complex thing requires geospatial approach for effective planning and assessment. Geospatial technique for visualization is an innovation and emerging discipline and a valuable tool to recognized the dynamic assessment of tourism, by integrating geospatial data as well as non spatial data in the form of a map display as an outcome. Geospatial visualization approach necessitates the planning which is based on the needs, goals, formulation, monitoring and evaluation of an action plan or programmes. Present study practices a geovisualization of dynamic assessment of tourism in Bageshwar district by integration of spatial and non-spatial data and also explores the suggestions to develop the tourism industry. The study investigated a case study in Bageshwar district. Study area has extensive potentialities for expansion of tourism industry, so in the region there is need to make efforts in this direction and make region more attractive and suitable for tourist as well as region itself. In the present study, an approach has been described the socio-economic development and growth analysis in the study area on account of tourism by linking the geospatial data (spatial & non-spatial). It can be done through the tourist growth. Growth analysis is done through attribute data, as domestic and international tourist arrival data calculated by compound annual growth rate (CAGR) and coefficient of variation that correlates with geospatial data using GIS as tool. The present study presents the tourism development in context of impact aspect and geovisualization done by tourism growth and tourist variation map. The finding reveals that the growth of tourist arrival increased to 3.54 percent during the year 2000 to 2010. The growth of kausani, Baijnath and Bageshwar tourist places of Bageshwar district also shows increment in the annual growth. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>